Expression Pattern and Functional Analyses of Arabidopsis Guard Cell-Enriched GDSL Lipases - Xiao, Chuanlei; Guo, Huimin; Tang, Jing; Li, Jiaying; Yao, Xuan; Hu, Honghong (Frontiers in Plant Science, 2021)
ABSTRACT There are more than 100 GDSL lipases in Arabidopsis, but only a few members have been functionally investigated. Moreover, no reports have ever given a comprehensive analysis of GDSLs in stomatal biology. Here, we systematically investigated the expression patterns of 19 putative Guard-cell-enriched GDSL Lipases (GGLs) at various developmental stages and in response to hormone and abiotic stress treatments. Expression pattern analyses showed that these GGLs had diverse expressions. Fifteen GGLs were highly expressed in guard cells, with seven preferentially in guard cells. Most GGLs were localized in endoplasmic reticulum, and some were also localized in lipid droplets and nucleus. Some closely homologous GGLs exhibited similar expression patterns at various tissues and in response to hormone and abiotic stresses, or similar subcellular localization, suggesting the correlation of expression pattern and biological function, and the functional redundancy of GGLs in plant development and environmental adaptations. Further phenotypic identification of ggl mutants revealed that GGL7, GGL14, GGL22, and GGL26 played unique and redundant roles in stomatal dynamics, stomatal development, and plant water relation. The present study provides unique resources for functional insights into these GGLs to control stomatal dynamics and development, plant growth, and adaptation to the environment.